Economic burden and mental health of primary caregivers of perinatally HIV infected adolescents from Kilifi, Kenya - Patrick V. Katana; Amina Abubakar; Moses K. Nyongesa; Derrick Ssewanyana; Paul Mwangi; Charles R. Newton; Julie Jemutai (BMC, 2020)
Abstract Background Eighty per cent of perinatally HIV infected (PHI) adolescents live in sub-Saharan Africa (sSA), a setting also characterized by huge economic disparities. Caregiving is crucial to the management of chronic illness such as HIV/AIDS, but the economic costs and mental disorders borne by caregivers of PHI adolescents often go unnoticed. In this study, we evaluated economic costs, coping strategies and association between economic cost and mental health functioning of caregivers of perinatally HIV infected adolescents in Kilifi, Kenya. Methods We used a cost of illness descriptive analysis approach to determine the economic burden and Patient Health Questionnaire (PHQ-9) to assess the caregivers' mental health. Cross-sectional data were collected from 121 primary caregivers of PHI adolescents in Kilifi using a structured cost questionnaire. Economic costs (direct and indirect costs) were measured from primary caregivers' perspective. We used descriptive statistics in reporting the results of this study. Results Average monthly direct and indirect costs per primary caregiver was Ksh 2784.51 (USD 27.85). Key drivers of direct costs were transportation (66.5%) and medications (13.8%). Total monthly costs represented 28.8% of the reported caregiver monthly earnings. Majority of the caregivers borrowed resources to cope with high economic burden. About 10.7% of primary caregivers reported depressive symptoms. Caregivers with positive depression screen (PHQ-9 score ≥ 10) had high average monthly direct and indirect costs. However, this was not statistically different compared to costs incurred by caregivers who screened negative for depressive symptoms. Conclusion Our study indicates that HIV/AIDS is associated with a significant economic burden for caregivers of adolescents living with HIV. Results underscore the need for developing economic empowerment and social support programmes that reduce the economic burden of caring for perinatally infected adolescent. These efforts may improve the mental health and quality of life of caregivers of adolescents living with HIV.